SPSS for Psychologists / A Guide to Data Analysis Using SPSS for Windows - Brace Nicola; Kemp Richard; Snelgar Rosemary (Houndmills, UK Palgrave Macmillan, 2006)
This book carefully leads the reader through the process of using SPSS to analyse psychological data. Dedications, Preface, Acknowledgements, Introduction, Data Entry in SPSS, Tests of Difference for Two Sample Designs, Tests of Correlation, Tests for Nominal Data, Data Handling, Analysis of Variance, Multiple Regression, Analysis of Covariance and Multivariate Analysis of Variance, Discriminant Analysis and Logistic Regression, Factor Analysis and Reliability and Dimensionality of Scales, Beyond the Basics, Glossary, References, Data Files, Defining a Variable in SPSS Versions 8 and 9, Adding Regression Lines to Scattergrams before Version 12, Index.